PENINGKATAN HASIL BELAJAR TEMA KAYANYA NEGERIKU MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE STAD PADA SISWA KELAS IV SEKOLAH DASAR - Wati, Yulis Maulia; Al-Haddar, Gamar (Teacher Training and Education Faculty, of Widya Gama Mahakam Samarinda University, 2020)
This study aims to learning achievement of My Country's Diversity theme through STAD Type Cooperative Learning Model on Fourth Grade Students of SDN 001 North Samarinda in Academic Year 2018/2019. This is a CAR that is carried out in III cycles and each cycle consists of 2 meetings. The results show that (1) the implementation of the STAD type of cooperative learning model can improve cognitive learning achievement. It can be seen from the average value of the class in the first cycle of 72.96 with a percentage of completeness of 40.74%, in the second cycle increased to 75 with a percentage of completeness of 70.37%, in the third cycle, it increase to 81.11 with a percentage of completeness of 92.59% . (2) Improve students’ activity. It is proven by the results of observations of the students’ activities in the first cycle that obtained the spirit aspect was 63%, attention was 64%, cooperation was 66%, activity was 65%. In the second cycle, there was 73% enthusiasm, 76% attention, 72% cooperation, 75% activity. In the third cycle, there was 87% enthusiasm, 81% attention, 84% cooperation, 86% activity.